1997
DOI: 10.1063/1.120260
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dose rate on interstitial release from the end-of-range implant damage region in silicon

Abstract: Low temperature molecular beam epitaxy was used to grow boron doping superlattices DSLs in Si, with peak boron concentrations of 110 18 /cm 3 , and spike widths of 10 nm. Amorphization of these DSLs was achieved using a series of Si implants of 30 and 112 keV, each at a dose of 1 10 15 /cm 2 , which placed the amorphous to crystalline interface between the first and second doping spikes. The dose rate of the Si implants was varied from 0.13 to 1.13 mA/cm 2. Post-implantation anneals were performed in a rapid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The annealing conditions were designed to cause known defect transformations that are known to occur in conventional (broad area implantation) samples. [20][21][22][23][24] We expect that the defect types are similar for the FIB-implanted specimens in this work, as we are comparing similar implanted doses of ions and annealing temperatures and time.…”
Section: Methodsmentioning
confidence: 86%
“…The annealing conditions were designed to cause known defect transformations that are known to occur in conventional (broad area implantation) samples. [20][21][22][23][24] We expect that the defect types are similar for the FIB-implanted specimens in this work, as we are comparing similar implanted doses of ions and annealing temperatures and time.…”
Section: Methodsmentioning
confidence: 86%
“…We believe that this is related to the known dependence of end-of-range dislocation loop densities upon implant fluxes. This modifies the flux of Si point defects or implant species from the implanted region, as these loops serve to trap diffusing species [34].…”
Section: Dislocation±point Defect Interactionsmentioning
confidence: 99%
“…It was shown that the interstitial flux from the EOR damage is approximately an order of magnitude greater into the substrate than toward the surface for overlapping 112-keV and 30-keV Si + implants to 1 ϫ 10 15 cm 2 performed at ͑20± 1͒°C. 32 The decrease in the interstitial flux toward the surface was attributed to the EOR damage acting as interstitial traps, which prevent a significant fraction of the interstitials from diffusing toward the substrate surface. Jones et al correlated the EOR dislocation loop density with the amount of interstitial backflow toward the surface, which increased with decreasing implant temperature ͑presumably due to the fact that less EOR damage is available to prevent the interstitials from diffusing toward the substrate surface͒.…”
Section: Discussionmentioning
confidence: 99%